Vertical effects of fiscal rules: The Swiss experience - Heiko T. Burret; Lars P. Feld (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2016)
Formal fiscal rules have been introduced in many countries throughout the world. While most studies focus on the intra-jurisdictional effects of fiscal rules, vertical effects on the finances of other levels of government have yet to be explored thoroughly. This paper investigates the influence of Swiss cantonal debt brakes on municipal finances during the years 1980-2011 by examining aggregated and disaggregated local data. A Difference-in-Differences estimation (twoway fixed effects) provides little evidence that budget constraints at the cantonal level affect average municipal finances and fiscal decentralization.
Keywords: H60; H77; H74; H72; 330; Fiscal Rule; Vertical Effect; Fiscal Shock; Decentralization; Sub-national Finances